PENERAPAN GOOD AGRICULTURE PRACTICE MELALUI SEKOLAH LAPANG KAKAO DI DESA KALIMBUA KECAMATAN TAPANGO KABUPATEN POLEWALI MANDAR SULAWESI BARAT - Karim, Harli; Iqraini, Nurul; Hamzah, Hamzah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2024)
Cocoa productivity in Indonesia is still low. The average productivity of cocoa plants at the farmer level is only in the range of 600-800 kg/ha/year. Whereas, the genetic potential of various cocoa clones can reach 2000-3000 kg/ha/year. Cocoa planting in Kalimbua Village began in 1980. The cultivation techniques used by farmers in Kalimbua Village are still simple. Cocoa planting in Kalimbua Village began in 1980. The cultivation techniques used by farmers in Kalimbua Village are still manual. Cocoa production uses excessive chemicals. Cocoa production with minimal chemicals is essential. One solution is the implementation of Good Agriculture Practice. Methods for implementing the program include: 1). Program socialization 2). Plot demo 3). Nursery 4). Field School. Results: There is an increase in knowledge and skills of partners in implementing Good Agriculture Practice. in Kalimbua Village, Tapango District, Polewali Mandar Regency